Chemistry for a Clean and Healthy Planet - Ramasami, Ponnadurai; Gupta Bhowon, Minu.; Jhaumeer Laulloo, Sabina; Li Kam Wah, Henri; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
These proceedings gather carefully selected, peer-reviewed contributions from the International Conference on Pure and Applied Chemistry (ICPAC 2018). The event, the latest installment in a biennial conference series, was held in July 2018 in Mauritius. The respective chapters in this unique collection reflect a wide range of fundamental and applied research in the chemical sciences and various interdisciplinary subjects. In addition to reviews, they highlight cutting-edge advances. .
Emerging Phytochemicals and Bioactive Compounds from a Desert Plant Prosopis cineraria (L.) Druce and Future Prospects -- Conductimetric Analysis and Preliminary Evaluation of Phytochemical Constituents of Sporobolus spicatus (Vahl) Kunth [Family: Poaceae] by FTIR and UV-Vis Spectroscopic Techniques -- The Molecular Dynamics Simulation of a Multi-Domain Outer Membrane Protein A (OmpA) from Shigellaflexneriin POPE Lipid Bilayer -- Photodegradation of Phenol by Silver Doped TiO2; A Comparative Study of the Efficiency of HPLC and UV-Vis Analyses.
Keywords: Analytical chemistry; Chemistry, Organic; Inorganic chemistry; Physical chemistry; Green chemistry; Analytical Chemistry; Organic Chemistry; Inorganic Chemistry; Physical Chemistry; Green Chemistry